Empowerment of MSMEs 'Es Kelapa Muda Duo Putri' Through Packaging Innovation and Digital Marketing in Kureksari Village: Pemberdayaan UMKM 'Es Kelapa Muda Duo Putri' Melalui Inovasi Kemasan dan Digital Marketing di Desa Kureksari - Mochammad Rifky; Afifatus Solikha (CV Yazri Aksara Nusantara, 2025)
This Community Service activity was carried out to increase the competitiveness and independence of Micro, Small and Medium Enterprises (MSMEs) Es Kelapa Muda Duo Putri in Kureksari Village, Sidoarjo, through packaging innovations and digital marketing strategies. The background of this activity departs from the problem of partners who still use plain packaging without brand identity and conventionally limited promotional strategies. The purpose of this activity is to empower partners to be able to develop highly competitive products by utilizing information technology. The implementation method uses a participatory approach through observation stages, interviews, packaging innovation training, social media management assistance, and evaluation of activity results. The results of the activity show a significant increase in the appearance of products with new packaging with logos and attractiveness, as well as an increase in the ability of partners to use social media as a means of promotion. This activity not only has a practical impact in the form of increasing sales and product image, but also strengthens digital literacy and innovative awareness of business actors. Overall, this PKM activity contributes to strengthening the community-based creative economy and becomes a replication model for the empowerment of MSMEs in other regions that have similar characteristics.